FACTORS INFLUENCING HEALTH LITERACY OF PESTICIDE USE AMONG DURIAN FARMERS, THA SALA DISTRICT, NAKHON SI THAMMARAT PROVINCE - Jankaew, benjawan; Khammaneechan, Patthanasak; Kaewsawat, Supreecha (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2021)
This research aimed to investigate the level of health literacy and analyze the factors influencing the health literacy of pesticide usage. The samples were 274 durian farmers from Thasala District, Nakhon Si Thammarat Province using systematic random sampling. The instruments were questionnaires, including the knowledge, attitudes, and health literacy of pesticide usage among durian farmers. All research instruments were validated in terms of content validity by three experts in the field. The reliability using Cronbach’s alpha were .85, .83, and .91, respectively. The data were analyzed using descriptive statistics and stepwise multiple regression analysis. The results were follows: 1) Overall, the health literacy of pesticide usage among durian farmers was at a high level (M = 3.99, SD = .43), 2) the factors influencing health literacy of pesticide usage among durian farmers were the attitudes of pesticide usage, the use of self-protection equipment against exposure to pesticides, and the female gender. These factors could predict 14.3% of the variance of health literacy about pesticide usage (R2 = .143, R2Adjusted = .134, p = .000). This research could be applied to create a health literacy enhancement program on the use of pesticides so that durian farmers will have health literacy and guidelines on the proper use of pesticides.